Design and fabrication of motor holding device for the prevention of unsafe working conditions in heat setting machines of textile industries. (2022) - Sankaranarayanan, R.; Surendar, N.; Rajesh Jesudoss Hynes, N.
Abstract: The textile industry is an unavoidable sector in our country. The respective sector can directly and indirectly create employment for millions of workers which covers both educated and uneducated people. Especially, the textile industry has a large number of uneducated workers. Factories should be established to prevent accidents in the industry so that unsafe conditions can be eliminated. The unsafe working conditions in various processes in the textile industry are detected and evaluated with the help of Hazard Identification and Risk Assessment (HIRA) [1] and initiatives are required to control the risk ratio accurately. Appropriate training should be provided to workers and work handling to deal with unsafe working conditions in the textile industry. The main problems associated with workers are the accidents which occur when dealing with excess weight [2] . Either necessary equipment to be deployed to handle excess weight or else the equipment should be designed as needed [3] . The purpose of the present research work is to identify hazards in the heat setting machine in the knitting department in the textile industry and design safety equipment to prevent them. There are about 14 motors in a Heat setting machine. These heavy motors lead to accident while handling motors in the absence of material handling equipment. The present work addresses this concern and a motor holding device has been designed and fabricated at low cost and analysis on this device has been carried out in ANSYS platform [3] . The motor holding device is designed and fabricated to carry the motor of 75 kg and maximum 1000 N force. The device is then configured and attached to the hand pallet truck to enable it to operate. The present device can be used by an individual worker safely and efficiently to complete the task using an attached hand pallet truck.